2018
DOI: 10.1111/cen.13848
|View full text |Cite
|
Sign up to set email alerts
|

Safety of calcium and vitamin D supplements, a randomized controlled trial

Abstract: Objective It is anticipated that an intake of vitamin D found acceptable by Endocrine Society Guidelines (10 000 IU/day) with co‐administered calcium supplements may result in frequent hypercalciuria and hypercalcaemia. This combination may be associated with kidney stones. The objective of this study was to compare the episodes of hypercalciuria and hypercalcaemia from calcium supplements co‐administered with 10 000 IU or 600 IU vitamin D daily. This design allows a comparison of the Institute of Medicine rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 41 publications
3
53
0
1
Order By: Relevance
“…11 The treatment did not reduce significantly bone fractures but an increased kidney stone risk has been described in women who received calcium and vitamin D. Recent studies confirmed that vitamin D, especially when prescribed in addition to calcium supplementation, increases significantly urine calcium excretion and in some studies the risk to develop kidney stones. 12,13 By contrast, some studies did not identify an increased risk of kidney stone after exposure to vitamin D alone (without calcium supplementation) during a median follow-up of 3.3 years. 25 Interventional studies remain sparse but recent observations show that some kidney stone formers may develop hypercalciuria after vitamin D "repletion".…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…11 The treatment did not reduce significantly bone fractures but an increased kidney stone risk has been described in women who received calcium and vitamin D. Recent studies confirmed that vitamin D, especially when prescribed in addition to calcium supplementation, increases significantly urine calcium excretion and in some studies the risk to develop kidney stones. 12,13 By contrast, some studies did not identify an increased risk of kidney stone after exposure to vitamin D alone (without calcium supplementation) during a median follow-up of 3.3 years. 25 Interventional studies remain sparse but recent observations show that some kidney stone formers may develop hypercalciuria after vitamin D "repletion".…”
Section: Discussionmentioning
confidence: 98%
“…11,12 A recent randomized controlled trial has shown that the recommended upper serum level of vitamin D, when associated with calcium supplements, results frequently in hypercalciuria. 13 Vitamin D, with or without calcium supplements, is prescribed to prevent bone mass loss, although randomized and controlled studies failed to evidence a protective role of vitamin D against fractures. 14,15 A few reports suggested that kidney stone formers with Randall's plaques may have an increased biological response to vitamin D but there is little evidence that vitamin D promotes or aggravates Randall's plaque formation to date.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 17 studies involving intervention with vitamin D supplements were identified, which are presented in Table 1 . Participants’ (n = 4482) mean age varied from 43 to 75 years, and the durations of the studies ranged from 8 weeks to 3 years [ 18 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. In seven studies, only females were included [ 18 , 32 , 33 , 34 , 35 , 36 , 37 ], in two studies, only males were included [ 38 , 39 ], while in the remaining eight studies, both sexes were included [ 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D supplements also present the same confusion. Some studies have also pointed out that vitamin D increases hypercalciuria ( Aloia et al, 2018 ). On the contrary, It is also reported that the increase of urinary calcium is not associated with increased serum vitamin D and may result from other factors, such as dietary factors ( Taheri et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%